Host-Seeking Behavior of Aphidius gifuensis (Hymenoptera: Braconidae) Modulated by Chemical Cues Within a Tritrophic Context. Issue 3 (28th May 2021) - Song, Yunzhe; Liu, Changming; Cai, Pumo; Chen, Weibin; Guo, Yaqing; Lin, Jia; Zhang, Shufang
Abstract: Aphidius gifuensis Ashmaed is a generalist endoparasitoid that parasitizes a variety of aphid species. In China, it is widely used as a biological control agent to protect vegetables and tobaccos in open fields; control efficiency is largely dependent on its host-seeking ability. In this study, a six-choice olfactometer was used to investigate the olfactory responses of A. gifuensis to tobacco plants that had suffered damage (either varying degrees of mechanical damage or from aphid-feeding at different time intervals) and tobacco volatiles with different dosages. Furthermore, the regularity of A. gifuensis females' response toward an aphid/tobacco complex was monitored using a Y-tube olfactometer. Our findings suggest that tobacco plants are significantly attractive to A. gifuensis after they have been punctured with 50 holes, or housed with Myzus persicae (Sulzer) at a density of 400 aphids, except at an infestation time of 12 h. Moreover, aphid density had a more significant effect on the response than the time interval since aphid application. Aphidius gifuensis was found to be active during the daytime and preferred to search for their aphid hosts at 14:00 h. Five EAG-active tobacco volatiles (trans-2-hexenal, methyl salicylate, benzaldehyde, cis-3-hexen-1-ol, and 1-hexanal) were found to significantly attract A. gifuensis females at different concentration ranges. The practical implications of these results are discussed in the framework of the sustainable biological control of pest aphids in agricultural production systems. Graphical Abstract: